دراسة حول ترجمة المشترك اللفظي في القرآن الكريم إلى اللغة الصينية: لفظ "فتح" أنموذجاً / A study on translating the polysemy in the Noble Qur’an into the Chinese language: The case of the word “Fataḥ” - maghraby mahmoud sayed, sayed (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2021)
مُلخَّص البحث: يحتوي القرآن الكريم على عدد كبير من الألفاظ متعددة المعاني أو ما يعرف بالمشترك اللفظي، ويواجه مترجم معاني القرآن الكريم عند ترجمته للمشترك اللفظي عدة تحديات تتبلور في كيفية تحديده للمعنى المراد للفظ في ضوء السياق القرآني، فضلاً عن كيفية اختياره للمعنى المكافئ في اللغة المترجم إليها، ونظراً إلى أأهمية دراسة طرق وأساليب ترجمة المشترك اللفظي في القرآن الكريم في مجال دراسة ترجمات معاني القرآن الكريم، فقد اعتمد البحث المنهج التحليلي المقارن من خلال إجراء دراسة تحليلية مقارنة لأساليب الترجمة التي طبقها كلاً من"محمد مكين 马坚" و"وانغ جينغ تجاي王静斋" عند ترجمة أحد ألفاظ المشترك اللفظي وهو لفظ"فتح"في القرآن الكريم إلى اللغة الصينية، وذلك بهدف معرفة طرق الترجمة التي اتبعها المترجمان عند ترجمة المشترك اللفظي في القرآن الكريم إلى اللغة الصينية، وهل نجحا في إيصال المعنى المراد للفظ "فتح" حسب سياقاته المختلفة إلى القارئ الهدف أم لا. وقد خلص البحث من خلال عرضه لأساليب ترجمة لفظ "فتح" في القرآن الكريم إلى اللغة الصينية إلى أن المترجمين قد أخذا بعين الاعتبار المعاني الدلالية المختلفة لهذا اللفظ حسب سياقاته المختلفة، معتمدين في ذلك على تفسير لفظ "فتح" في مواضعه المختلفة، إلا أن محمد مكين سعى أكثر من وانغ جينغ تجاي إلى تطبيق طريقة الترجمة المعنوية أو ما يعرف بالترجمة التفسيرية عند نقله للمعاني المختلفة للفظ "فتح" إلى اللغة الصينية؛ من أجل نقل المعنى المراد من اللفظ في سياقاته المختلفة؛ بينما مال وانغ جينغ تجاي إلى إلتزام الترجمة الحرفية في مواضع كثيرة، وقد تسبب هذا في حدوث حالة من اللبس والغموض في فهم المعنى المراد في بعض المواضع. الكلمات المفتاحية: المشترك اللفظي، لفظ "فتح" في القرآن الكريم، ترجمة معاني القرآن إلى اللغة الصينية، محمد مكين، وانغ جينغ تجاي. Absract The Holy Qur’an contains many words with multiple meanings, or what is known as polysemy. When translating the meanings of the Holy Qur’an, the translator faces several challenges to determine the intended meaning of the polysemy in the light of the Qur’anic context, in addition to how he chooses the equivalent meaning in the language into which it is translated. The research adopted the comparative analytical method by conducting a comparative analytical study of the methods of translation applied by both “Muhammad Makin 马坚” and “Wang Jing Zhai 王静斋” when translating one of the polysemy, which is the word “fataḥ” in the Holy Qur’an into the Chinese language, with the aim of knowing the translation methods that the translators followed when translating the polysemy in the Holy Qur’an into the Chinese language, and whether they succeeded in conveying the intended meaning of the term “fataḥ” according to its different contexts to the target reader or not. The research concluded, by presenting the methods of translating the word “fataḥ” in the Holy Qur’an into Chinese, that the translators had taken into consideration the different semantic meanings of this word according to its different contexts, relying on the interpretation of the word “fataḥ” in its various places, except that Muhammad Makeen More than Wang Jing Zhai sought to apply the method of semantic translation or what is known as interpretive translation when translating the different meanings of the word " fataḥ " into the Chinese language in order to convey its intended meaning in its different contexts, while Wang Jing Zhai tended to commit to literal translation in many places. In some cases, this may cause confusion and ambiguity in understanding the intended meaning. Keywords: polysemy, the word "open" in the Holy Qur'an, translation of the meanings of the Qur'an into the Chinese language, Muhammad Makin, Wang Jing Zhai. Abstrak Al-Quran mengandungi banyak perkataan yang mempunyai pelbagai makna, yang dikenali sebagai polisemi. Apabila menterjemah makna Al-Quran, penterjemah menghadapi beberapa cabaran untuk menentukan maksud polisemi yang dimaksudkan dalam konteks Al-Quran, di samping cabaran memilih makna yang setara dalam bahasa sasar yang berkenaan. Penyelidikan ini menggunakan kaedah analisis perbandingan dengan menjalankan kajian analitikal perbandingan kaedah penterjemahan yang digunapakai oleh dua penterjemah “Muhammad Makin 马坚” dan “Wang Jing Zhai 王静斋” dalam menterjemah satu polisemi, iaitu perkataan “fataḥ” dalam Al-Quran ke dalam bahasa Cina. Kajian ini bertujuan untuk mengetahui kaedah terjemahan yang diguna oleh kedua-dua penterjemah semasa menterjemah polisemi tersebut dalam Al-Quran ke dalam bahasa Cina, sama ada mereka berjaya menyampaikan maksud yang diinginkan mengikut konteksnya yang berbeza kepada pembaca sasaran. Kajian ini menyimpulkan, dengan mengemukakan kaedah penterjemahan perkataan “fataḥ” dalam Al-Quran ke dalam bahasa Cina, penterjemah telah mengambil kira makna semantik yang berbeza bagi perkataan ini mengikut konteks yang berbeza, bergantung pada tafsiran perkataan “fataḥ” di pelbagai tempatnya, kecuali Muhammad Makeen yang lebih banyak daripada Wang Jing Zhai dalam menggunakan kaedah terjemahan semantik atau yang dikenali sebagai terjemahan tafsiran apabila menterjemahkan makna yang berbeza bagi perkataan "fataḥ " ke dalam bahasa Cina untuk menyampaikan maksud yang dimaksudkan dalam konteks yang berbeza, manakala Wang Jing Zhai pula lebih cenderung melakukan terjemahan literal di banyak tempat. Dalam sesetengah kes, ini boleh menyebabkan kekeliruan dan kekaburan dalam memahahami maksud yang diinginkan. Kata kunci: polisemi, perkataan "terbuka" dalam Al-Quran, terjemahan makna Al-Quran ke dalam bahasa Cina, Muhammad Makin, Wang Jing Zhai.